Adaptive Leadership dan Etos Kerja Terhadap Produktivitas Kerja Karyawan : Psikologi Capital Sebagai Variabel Mediasi - Nur Layli Fatikhatun Nissa; Wahyu Eko Pujianto (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to determine the relationship between adaptive leadership, work ethic and employee work productivity with psychological capital as a mediating variable. The method used in this research is a quantitative method. Data collection was carried out by random sampling by distributing questionnaires to PT employees. Japfa Comfeed Indonesia, Tbk which is then processed using SmartPLS. The natural population of this research are employees who work at PT. Japfa Comfeed Indonesia, Tbk with a sample size of 50 people.